2020
DOI: 10.33221/jikes.v19i03.598
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antibakteri Ekstrak Etanol Daun Akar Kaik-Kaik (Uncaria cordata (Lour.) Merr.) terhadap Staphylococcus aureus dan Salmonella typhi.

Abstract: Akar kaik-kaik (Uncaria cordata (Lour.) Merr.) adalah tumbuhan yang daunnya mengandung senyawa aktif seperti tanin, saponin dan flavonoid. Penelitian ini bertujuan untuk mengetahui aktivitas antibakteri ekstrak etanol daun akar kaik-kaik (Uncaria cordata (Lour.) Merr.) terhadap Staphylococcus aureus dan Salmonella typhi. Ekstrak dibuat secara maserasi serbuk daun akar kaik-kaik dalam etanol 96%. Uji aktivitas antibakteri dilakukan dengan metode difusi cakram pada media Nutrient Agar (NA) dan konsentrasi hambat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
2
1
7
Order By: Relevance
“…The difference results between E. coli and S. typhi against the akar kaik-kaik leaves extract probably due to the presence of flavonoid in extract. Our results showed no flavonoid content, while Rachmatiah et al [38] showed positive in flavonoid test. Flavonoid could interrupt the bacterial cell wall and membrane of microorganisms.…”
Section: Antimicrobial Activitycontrasting
confidence: 59%
See 2 more Smart Citations
“…The difference results between E. coli and S. typhi against the akar kaik-kaik leaves extract probably due to the presence of flavonoid in extract. Our results showed no flavonoid content, while Rachmatiah et al [38] showed positive in flavonoid test. Flavonoid could interrupt the bacterial cell wall and membrane of microorganisms.…”
Section: Antimicrobial Activitycontrasting
confidence: 59%
“…Flavonoids were more dissolved in 96% ethanol rather than at 70% ethanol [36,37]. This assumption was also supported by the result of Rachmatiah et al [38], which showed a positive result in flavonoid screening in 96% ethanol extract of akar kaik-kaik leaves.…”
Section: Phytochemicals Screeningmentioning
confidence: 73%
See 1 more Smart Citation
“…Tumbuhan kaik-kaik yang berasal dari hutan larangan adat Kabupaten Kampar, Riau mempunyai beberapa aktivitas diantaranya ekstrak etanol daun mempunyai aktivitas sebagai antibakteri terhadap bakteri Staphylococcus aureus dan Salmonella typhi [13] , ekstrak etanol daun ini juga mempunyai aktivitas terhadap bakteri Staphylococcus aureus, Escherichia coli dan Candida albicans [14] . Ekstrak etanol dari akarnya mempunyai aktivitas yang dapat menurunkan kolesterol pada mencit jantan putih dengan dosis terbaik pada 200 mg/kgBW [15] .…”
Section: Pendahuluanunclassified
“…Skrining fitokimia yang dilakukan meliputi pemeriksaan alkaloid, flavonoid, fenolik, saponin, steroid dan terpenoid [13], [18], [20] .…”
Section: Skrining Fitokimiaunclassified